Penerapan Mobilisasi Dini pada Ibu Post Sectio Caesarea terhadap Penurunan Nyeri Pasca Operasi di Ruang Nifas RS Budi Rahayu Pekalongan Tahun 2025 - Lutfiyaningsih, Lutfiyaningsih; Desi Risqiani; Dumilah Urip; Elisabet Indah Lestari; Heni Prasetyorini (CV SCRIPTA INTELEKTUAL MANDIRI, 2026)
This study aimed to analyze the effect of early mobilization on postoperative pain reduction among post-cesarean mothers in the maternity ward of Budi Rahayu Hospital Pekalongan in 2025. A quasi-experimental design with a one-group pretest–posttest approach was applied involving post-cesarean mothers within 24–48 hours after surgery. Data were collected using the Numeric Rating Scale to measure pain intensity and observational sheets to assess functional mobility. The findings indicated a significant decrease in pain intensity following the implementation of early mobilization, supported by physiological mechanisms such as improved blood circulation, reduced muscle tension, and endorphin stimulation. In addition, several determinants including family support, patient knowledge, and healthcare provider involvement contributed to the effectiveness of the intervention. Early mobilization also demonstrated clinical implications in preventing postoperative complications and enhancing functional recovery. These results highlight the importance of integrating physical, psychological, and social approaches in nursing care to optimize recovery outcomes among post-cesarean patients.